In the previous section, we saw the basic details about Pascal's triangle. We saw the necessity for developing a rule to find the various numbers in the Pascal's triangle. In this section, we will see such a rule.
The basics about the rule can be written in 6 steps:
1. We have seen the concept of combination in the previous chapter.
We saw the formula: nCr = n!r!(n−r)!
2. Let us check whether this formula is applicable to the Pascal's triangle. The triangle is shown below for easy reference:
![]() |
Fig.8.2 |
The check can be done in 3 steps:
(i) Consider any coefficient in the Pascal's triangle, say the fourth coefficient for index 5
♦ The fourth coefficient of index 5 is 10
♦ 5C3 is also 10
(ii) Consider any other coefficient in the Pascal's triangle, say the third coefficient for index 7
♦ The third coefficient of index 7 is 21
♦ 7C2 is also 21
(iii) Let us check one more coefficient in the Pascal's triangle, say the fifth coefficient for index 8
♦ The fifth coefficient of index 8 is 70
♦ 8C4 is also 70
3. This gives us an idea to pick out any coefficient in the Pascal’s triangle:
The xth coefficient for any index n will be nCx-1
• For example, let n be 6 and x be 5
♦ Then the 5th coefficient of index 6 will be be 6C5-1 = 6C4 = 15
♦ From the Pascal's triangle, we see that, this is true.
4. Based on this information, the Pascal’s triangle can be modified as shown in fig.8.3 below:
![]() |
Fig.8.3 |
• In the modified triangle, we see two points:
(i) In any row, the subscript on the right side of ‘C’ progressively increases in the order: 0, 1, 2, 3, . . . n
♦ Where n is the index of that row.
(ii) In any row, the superscript on the left side of ‘C’ does not change.
♦ It is equal to n, the index of the row.
5. The above two points give us an idea to quickly write any row of the Pascal’s triangle.
• For example, based on the two points, the row for index 12 will be:
12C0, 12C1, 12C2, 12C3, 12C4, 12C5, 12C6, 12C7, 12C8, 12C9, 12C10, 12C11, 12C12
6. If we can write any row of the Pascal’s triangle quickly, we will be able to write the expansion corresponding to that index also quickly.
• Let us see an example:
Expand (a+b)7
Solution:
1. The coefficients will be:
7C0, 7C1, 7C2, 7C3, 7C4, 7C5, 7C6, and 7C7
2. So the expansion will be:
(a+b)7 =
7C0 a7 + 7C1 a6b1 + 7C2 a5b2 + 7C3 a4b3 + 7C4 a3b4 + 7C5 a2b5 + 7C6 a1b6 + 7C7 b7
• Remember that, the indices of a and b are calculated using the three peculiarities that we wrote in the previous section. They are given below for easy reference:
(i) The total number of terms in the expansion, is one more than the index. (ii) Powers of the first quantity ‘a’ go on decreasing by 1 whereas the powers of the second quantity ‘b’ increase by 1, in the successive terms. (iii) In each term of the expansion, the sum of the indices of a and b is the same and is equal to the index of (a+b). |
• Thus we can write the complete expansion.
Now we can write the general form. It can be written in 3 steps:
(i) All the coefficients are of the form nCr
♦ For any particular problem, ‘n’ will be a constant.
✰ It will be equal to the index in the question.
♦ r will increase from 0 to n
(ii) The indices of a and b are calculated using the three peculiarities that we wrote in the previous section (also shown in the box above).
(iii) Based on this, the general form will be:
(a+b)n = nC0an + nC1an−1b + nC2an−2b2 + nC3an−3b3 + . . . + nCn−1abn−1 + nCnbn
• Let us use this general form to expand (2x+5)6
We get:
(2x+5)6
=6C0(2x)650+6C1(2x)551+6C2(2x)452+6C3(2x)353+6C4(2x)254+6C5(2x)155+6C6(2x)056=6C026x650+6C125x551+6C224x452+6C323x353+6C422x254+6C521x155+6C620x056=6C0×64×x6×50+6C1×32×x5×51+6C2×16×x452+6C3×8×x3×53+6C4×4×x2×54+6C5×2×x155+6C6×1×x056=1×64×x6×50+6×32×x5×51+15×16×x4×52+20×8×x3×53+15×4×x2×54+6×2×x1×55+1×1×x0×56=1×64×x6×1+6×32×x5×5+15×16×x4×25+20×8×x3×125+15×4×x2×625+6×2×x1×3125+1×1×x0×15625=64x6+960x5+6000x4+20000x3+37500x2+37500x+15625
We have seen the general form. The RHS of that general form is a bit lengthy. It can be easily shortened as explained by the 4 steps below:
1. We see that, the RHS is a sum of a finite number of terms. So it is a summation.
• We can use the symbol '∑' (Greek upper case letter sigma) to denote summation. Thus the general form becomes:
(a+b)n = k=n∑k=0nCkan−kbk
2. We know that, for any particular problem, n will be a constant. It is the index.
3. k is not a constant. It takes different values in different terms.
• 'k=0' at the bottom of '∑' indicates that, the value of k starts from zero. In other words, the value of k in the first term is zero.
• 'k=n' at the top of '∑' indicates that, the value of k ends at
n. In other words, the value of k in the last term is n.
• So the values of k are: 0, 1, 2, 3, . . . n
• It is known as the summation from k = 0 to k = n.
4. The index of a is (n-k). The index of b is k.
This shows that, the sum of the indices of a and b will be n in every term.
Let us see some special cases:
Case 1:
In this case, we investigate the expansion when the second quantity is -ve. This can be written in 3 steps:
1. Let us put a = x and b = -y. Then we get:
(a+b)n = (x-y)n = [x + (-y)]n
2. Expanding this using the general form, we get:
[x+(−y)]n
=nC0xn(−y)0+nC1xn−1(−y)1+nC2xn−2(−y)2+nC3xn−3(−y)3+. . . + nCnx0(−y)n=nC0xn(−1)0y0+nC1xn−1(−1)1y1+nC2xn−2(−1)2y2+nC3xn−3(−1)3y3+. . . + nCnx0(−1)nyn
= k=n∑k=0nCk(−1)kxn−kyk
3. Based on the above result, we can write:
(a−b)n = k=n∑k=0nCk(−1)kan−kbk
◼ Let us expand (x-2y)5 using this result. We get:
(x−2y)5 = [x+(−2y)]5 = k=5∑k=05Ck(−1)kx6−k(−2y)k
• Once we write the sigma notation on the RHS, we will be able to write all the terms easily. We get:
(x−2y)5
=5C0x5(−1)0(2y)0+5C1x5−1(−1)1(2y)1+5C2x5−2(−1)2(2y)2+5C3x5−3(−1)3(2y)3+5C4x5−4(−1)4(2y)4+5C5x5−5(−1)5(2y)5=1×x5×1×(2y)0+5×x4×−1×(2y)+10×x3×1×(4y2)+10×x2×−1×(8y3)+5×x1×1×(16y4)+1×x0×−1×(32y5)=x5−10x4y+40x3y2−80x2y3+80xy4−32y5
Case 2:
In this case, we investigate the expansion when the first quantity is 1. This can be written in 3 steps:
1. Let us put a = 1 and b = x. Then we get:
(a+b)n = (1+x)n
2. Expanding this using the general form, we get:
(1+x)n
=nC01nx0+nC11n−1x1+nC21n−2x2+nC31n−3x3+. . . + nCn10xn=nC01nx0+nC11n−1x1+nC21n−2x2+nC31n−3x3+. . . + nCn10xn
= k=n∑k=0nCk1n−kxk
3. So we can write:
(1+x)n = k=n∑k=0nCkxk
◼ Let us expand (1+2x)6 using this result. We get:
(1+2x)6 = k=6∑k=06Ck(2x)k
• Once we write the sigma notation on the RHS, we will be able to write all the terms easily. We get:
(1+2x)6
=6C016(2x)0+6C1(2x)1+6C2(2x)2+6C3(2x)3+6C4(2x)4+6C5(2x)5+6C6(2x)6=1×(2x)0+6×(2x)+15×(4x2)+20×(8x3)+15×(16x4)+6×(32x5)+1×(64x6)=1+12x+60x2+160x3+240x4+192x5+64x6
◼ x = 1 is a special case coming under this category. We get:
(1+x)n = (1+1)n = 2n = k=6∑k=0nCkxk = k=6∑k=0nCk1k = k=6∑k=0nCk
• Once we write the sigma notation on the RHS, we will be able to write all the terms easily. We get:
= nC0 + nC1 + nC2 + nC3 + . . . + nCn
• So we can write:
2n = nC0 + nC1 + nC2 + nC3 + . . . + nCn
Case 3:
In this case, we investigate the expansion when the first quantity is 1 and the second quantity is -ve. This can be written in 3 steps:
1. Let us put a = 1 and b = -x. Then we get:
(a+b)n = (1-x)n = [1 + (-x)]n
2. Expanding this using the general form, we get:
[1+(−x)]n
=nC01n(−x)0+nC11n−1(−x)1+nC21n−2(−x)2+nC31n−3(−x)3+. . . + nCn10(−x)n=nC01n(−1)0x0+nC11n−1(−1)1x1+nC21n−2(−1)2x2+nC31n−3(−1)3x3+. . . + nCn10(−1)nxn
= k=n∑k=0nCk(−1)k1n−kxk
3. Based on the above result, we can write:
(1−x)n = k=n∑k=0nCk(−1)kxk
◼ Let us expand (1-2x)5 using this result. We get:
(1−2x)5 = [1+(−2x)]5 = k=5∑k=05Ck(−1)k(−2x)k
• Once we write the sigma notation on the RHS, we will be able to write all the terms easily. We get:
(1−2x)5
=5C0(−1)0(2x)0+5C1(−1)1(2x)1+5C2(−1)2(2x)2+5C3(−1)3(2x)3+5C4(−1)4(2x)4+5C5(−1)5(2x)5=1×1×(2x)0+5×−1×(2x)+10×1×(4x2)+10×−1×(8x3)+5×1×(16x4)+1×−1×(32x5)=1−10x+40x2−80x3+80x4−32x5
• We wrote: (1−x)n = k=n∑k=0nCk(−1)kxk
◼ x = 1 is a special case coming under this category. We get:
(1−x)n = (1−1)n = 0n = k=n∑k=0nCk(−1)k1k = k=n∑k=0nCk(−1)k
• Once we write the sigma notation on the RHS, we will be able to write all the terms easily. We get:
= nC0(−1)0 + nC1(−1)1 + nC2(−1)2 + nC3 + . . . + nCn(−1)n
• So we can write:
0n = nC0 − nC1 + nC2 − nC3 + . . . + (−1)n × nCn
In the next section we will see some solved examples.
Copyright©2022 Higher secondary mathematics.blogspot.com
No comments:
Post a Comment